Factors influencing patrons’ tipping practice at 5-star hotels in Kuala Lumpur, Malaysia / Mohammad Hafizi Md Rus...[et al.] - Md Rus, Mohammad Hafizi; Zain, Razlan Adli; Abdul Patah, Mohd Onn Rashdi; Zainal Abidin, Izhar Hafifi; Mohd Radzi, Salleh (Faculty of Hotel and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
This study investigates the factors influencing tipping practice in Kuala Lumpur 5-star hotels. Experienced customers of five star rated hotels were targeted in this investigation by focusing on two sub-dimensions of service component which are personal and professional dimensions. Service charges and good and service tax has been added in most premises bills raises question on why people tip. This study reports upon a study of 400 hotel customers. Using survey data, results indicated that professional aspect play the important role in tipping practice. The findings showed that the culture of tipping do exist in Malaysia especially in the city of Kuala Lumpur and this study contributes to the expansions of literature on tipping practice.